Combinatorics, statistics, probability calculus in the secondary school in Lithuania - Survila, Pranas (Lietuvos matematikos rinkinys, 2000)
The analysis of Lithuanian textbooks Qr combinatorics, statistics and elementary probability is presented. The methodological approach of the current teaching programme is discussed. The definitions of some notions are criticized and the alternatives suggested.